Radiology imaging in the hospice setting. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Beggan, Shane; Rayment, Clare; Ward, Jason
Abstract : Background: There is little literature available regarding the use of radiology services within the hospice setting. St Gemma's Hospice in Leeds has a 32-bed inpatient unit with around 600 admissions per annum and a day unit and outpatient service reviewing 400 patients a year. It accesses the local hospital trust for imaging. Aims: To collate all radiology requests over a year to determine the frequency of different imaging modalities and what proportion detected the anticipated result or an alternative explanation for symptoms. Secondary aims included the proportion of patients who died within 2 weeks of imaging and examining the cost of imaging. Method: Data were collected retrospectively from the radiology IT department at Leeds Teaching Hospitals NHS Trust. It included details of all imaging requested for inpatients and outpatients between 1/1/10 and 31/12/10 by Doctors within the hospice. Results: 51 patients had 62 scans: 21 CTs, 18 MRIs, 10 Ultrasound scans, 4 CXRs, 4 AXRs, 3 Nuclear bone scans and 1 barium swallow. The most common reasons for imaging were for possible brain metastases (13), or spinal cord compression (12), 29% and 25% respectively were positive. Imaging for venousthromboembolism (11), and disease progression (6), were the next most common reasons for scanning, 27% and 67% respectively were positive. Scans showed an explanation for symptoms in 5/12 (42%) for SCC, 5/13 (38%) for brain mets, 5/5 (100%) for PE and 5/6 (83%) for disease progression. 11% of patients died within 2 weeks of having their scan. The approximate total cost based on NHS average reference costs was just under £10, 000. Conclusion: Most scans were appropriately requested. Depending on the imaging between 25 and 100% showed some abnormality. Most imaging was avoided in the 2 weeks prior to a patient's death. The costs associated with imaging are significant.